PENGARUH PROPORSI MINYAK CUMI DAN MINYAK KEDELAI SEBAGAI SUMBER LEMAK DALAM PAKAN TERHADAP PERTUMBUHAN JUVENIL KEPITING BAKAU (Scylla paramamosain) - Muhammad Marzuqi; Ibnu Rusdi; Nyoman Adiasmara Giri; Ketut Suwirya (Jurnal Perikanan Universitas Gadjah Mada, 2006)
The purpose of this experiment was to know lipid sources requirement for growth of mud crab (Scylla paramamosain) juvenile. The experiment used ninety of juveniles reared in 30 l of seawater with flow-throught water system and aeration. Initial average body weight and carapace width of juveniles were 0.21 g and 1.05-1.07 cm, respectively. Juveniles were stocked individually using a supernet material in each tank. Five isoprotein and isoenergy formulated diet with dry pellet form containing different proportion of squid oil and soybean oil as lipid sources i.e. 12%:0%, 9%:3%, 6%:6%, 3%:9% and 0%:12%. Feed were given twice a day in the morning and afternoon. The results showed that proportion of dietary squid oil and soybean oil as lipid sources had significant effects on final body weight, weight gain, carapace width, feed efficiency and essential fatty acid of mud crab (P